Immune Checkpoint Inhibitors Plus an Anti-VEGF Antibody as the First-Line Treatment for Unresectable Hepatocellular Carcinoma: A Network Meta-Analysis and Cost-Effectiveness Analysis - Li, Lu; Yang, Shilei; Chen, Yanwei; Tian, Li; He, Ying; Wu, Bin; Dong, Deshi (Frontiers in Pharmacology, 2022)
Background: Sintilimab + a bevacizumab biosimilar (IBI305) (SB) and atezolizumab + bevacizumab (AB) have been approved for the treatment of unresectable hepatocellular carcinoma (HCC). At present, oncologists and their patients remain indecisive on their preferred treatment regime. Therefore, assessing their efficacy via a network meta-analysis and determining their comparative cost-effectiveness is necessary. Objective: To evaluate the cost-effectiveness of SB and AB compared with sorafenib alone for the treatment of unresectable HCC. Materials and Methods: The data used in our analysis were obtained from patients in ORIENT-32 and IMbrave150 phase III randomized clinical trials. A Bayesian network meta-analysis and cost-effectiveness analysis that included 1,072 patients were performed in this study. A partitioned survival model was applied to the patients with unresectable HCC. The model was designed with a 15-year time horizon, 1-month cycle, and 5% discount rate for costs and outcomes. In China, an incremental cost-effectiveness ratio (ICER) value of less than $33,500 (three times the GDP per capita in 2020) per quality-adjusted life-year (QALY) is considered cost-effective. The influence of parameter uncertainty on the results was verified by one-way deterministic sensitivity analysis and probability sensitivity analysis. Furthermore, scenario analyses of the patient assistance program (PAP) were conducted to explore the cost-effectiveness of SB and AB. Results: For the model of 1,072 patients, treatment with SB produced an additional 0.617 QALYs compared with sorafenib, resulting in an ICER of $39,766.86/QALY. Similarly, treatment with AB produced an additional 0.596 QALYs compared with sorafenib, resulting in an ICER of $103,037.66/QALY. The probability sensitivity analysis showed that when the willingness-to-pay (WTP) threshold was $33,500/QALY, the cost-effectiveness of SB and AB was 15.4 and 0.4%, respectively. However, in the scenario analyses, the probability of SB and AB regimens being cost-effective was 65.4 and 15.8%, respectively, at a WTP of $33,500/QALY. Conclusion: The findings from our study showed that sintilimab + a bevacizumab biosimilar is a cost-effective regimen compared with sorafenib as the first-line therapy for unresectable HCC in China at a $33,500 WTP threshold if sintilimab PAP is considered. However, the atezolizumab + bevacizumab regimen is not cost-effective whether atezolizumab PAP is considered or not.